2022
DOI: 10.3390/pharmaceutics14061214
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal β-Sitosterol Suppresses Metastasis of CT26/luc Colon Carcinoma via Inhibition of MMP-9 and Evoke of Immune System

Abstract: β-sitosterol (SITO) has been reported with anticancer effects; however, with poor bioavailability. The current study aimed to investigate whether liposomal encapsulated β-sitosterol (LS) has a better inhibition effect on tumor metastasis than β-sitosterol in a CT26/luc lung metastasis mouse model and the possible underlying mechanism. LS was liposomal-encapsulated SITO and was delivered to mice by oral gavage. The cell viability was determined by the MTT assay, and invasiveness of the tumor cells and related p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that β-sitosterol exerts anti-inflammatory and cholesterol-lowering effects. 30 It can also reduce the severity of NP in diabetic mice. 31 For these reasons, in the present work β-sitosterol was selected to explore the potential analgesic mechanism of LCH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that β-sitosterol exerts anti-inflammatory and cholesterol-lowering effects. 30 It can also reduce the severity of NP in diabetic mice. 31 For these reasons, in the present work β-sitosterol was selected to explore the potential analgesic mechanism of LCH.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 5 is a commonly occurring phytosterol called β-sitosterol, which is a key component present in plants. Out of the many pharmacological and biological effects that have been reported for this compound over the past decades, anti-inflammatory, angiogenic, antiadipogenic, anti-diabetic, anti-oxidant, anti-cancer, immunomodulatory activities and a role in cardiovascular diseases prevention can be mentioned, reported from recent findings that can be beneficial in drug developments and other therapeutic applications [45][46][47][48][49][50][51]. The hypocholesterolemic effects of E. hirta and its role in curing obesity have been linked to this natural compound [22], as well as the larvicidal activity of E. thymifolia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal encapsulated β-SITO (LS), synthesized by the thin-film hydration method using egg phosphatidylcholine (EPC), shows better invasion inhibition, lower cytotoxicity, and fewer metastases to other tissues compared with SITO when treating colon carcinoma. The inhibition of MMP-9 and the elicitation of anti-tumor immune response generated by LS further prove it to be a more promising anti-tumor drug [31].…”
Section: Natural Mmp-9 Inhibitors or Mmp-9 Inhibitory Molecules Appli...mentioning
confidence: 96%